Identification of microbial communities in rice wine traditional starter (sasad) and fermentation of rice wines - Koay Meiwei (2023)
Rice wine is a rice-based alcoholic beverage produced through the fermentation of cereal grains, mainly rice, with microbial starters. However, the starter cultures sold in the market are often prepared based on empirical knowledge and thus varied in microbial compositions. Their exact microbial contents are usually unknown, giving rise to the possibility of product quality and food safety issues. Although many researchers have identified the microbial communities in various rice wine starter cultures using molecular approaches, such information on sasad, a traditional starter culture for rice wine fermentation in Sabah, Malaysia, has not been published. Therefore, this research aims to identify the fungal and bacterial communities in sasad, study the physicochemical and microbiological changes in rice wines during fermentation, and determine the consumers’ acceptance of rice wines. The fungal and bacterial communities were identified through amplicon-based next-generation sequencing (NGS). Physicochemical properties including total soluble solids (TSS), alcohol content, total titratable acidity (TTA), pH, and colour, as well as microbiological properties such as total yeast and mould count (TYMC) and total lactic acid bacteria (LAB) count were determined. In addition, consumers’ acceptance of rice wines was determined through preference ranking and hedonic tests. A total of two fungal phyla (Mucoromycota and Ascomycota) with five genera (Mucor, Rhizopus, Saccharomycopsis, Wickerhamomyces, and Kodamaea) and two bacterial phyla (Proteobacteria and Firmicutes) with 10 genera (Kosakonia, Weissella, Enterobacter, Lactococcus, Pseudomonas, Bacillus, Chromobacterium, Paludibacterium, Enterococcus, and Gluconobacter) were identified as the core microbiota (relative abundance > 1.00%) in the sasad samples. Batch fermentation was successfully carried out using the sasad samples. The overall fermentation dynamics of rice wines (RWA, RWB, and RWC) produced using different sasad (SA, SB, and SC, respectively) exhibited similar trends. However, variations between the samples were still detected. After 28 days of ferementation, RWC showed the lowest TSS (22.9 ± 0.2 °Brix) and highest alcohol content (15.95 ± 0.07%), while RWA had the highest TTA (0.68 ± 0.04% lactic acid) and lowest pH (3.60 ± 0.01), demonstrating the effect of microbial compositions of sasad on the quality of final rice wines. All rice wine samples were acceptable to the panellists, while rice wines with darker shades of yellow and higher alcohol content or stronger alcoholic aroma were preferable. However, there is no significant difference (p > 0.05) in liking scores for taste, mouthfeel, and overall acceptance among the rice wine samples. The variation in consumers’ tastes suggested a potential for developing rice wines with various flavours to fulfil consumers’ needs. This research provides important insights into the potential roles of core microbiota found in sasad, the fermentation dynamics of rice wines, and the consumers’ acceptance of rice wines. The occurrence of opportunistic spoilage and pathogenic microorganisms in sasad emphasises the importance of developing sasad with well-defined microbial compositions for the consistent production of safe and high-quality rice wines.